Genes in S and T Subgenomes Are Responsible for Hybrid Lethality in Interspecific Hybrids between Nicotiana tabacum and Nicotiana occidentalis - Tezuka, Takahiro; Marubashi, Wataru (PLOS ONE, 2012)
Background Many species of Nicotiana section Suaveolentes produce inviable F1 hybrids after crossing with Nicotiana tabacum (genome constitution SSTT), a phenomenon that is often called hybrid lethality. Through crosses with monosomic lines of N. tabacum lacking a Q chromosome, we previously determined that hybrid lethality is caused by interaction between gene(s) on the Q chromosome belonging to the S subgenome of N. tabacum and gene(s) in Suaveolentes species. Here, we examined if hybrid seedlings from the cross N. occidentalis (section Suaveolentes)×N. tabacum are inviable despite a lack of the Q chromosome. Methodology/Principal Findings Hybrid lethality in the cross of N. occidentalis×N. tabacum was characterized by shoots with fading color. This symptom differed from what has been previously observed in lethal crosses between many species in section Suaveolentes and N. tabacum. In crosses of monosomic N. tabacum plants lacking the Q chromosome with N. occidentalis, hybrid lethality was observed in hybrid seedlings either lacking or possessing the Q chromosome. N. occidentalis was then crossed with two progenitors of N. tabacum, N. sylvestris (SS) and N. tomentosiformis (TT), to reveal which subgenome of N. tabacum contains gene(s) responsible for hybrid lethality. Hybrid seedlings from the crosses N. occidentalis×N. tomentosiformis and N. occidentalis×N. sylvestris were inviable. Conclusions/Significance Although the specific symptoms of hybrid lethality in the cross N. occidentalis×N. tabacum were similar to those appearing in hybrids from the cross N. occidentalis×N. tomentosiformis, genes in both the S and T subgenomes of N. tabacum appear responsible for hybrid lethality in crosses with N. occidentalis.